Specific features of immunity control of survey radar under its suppression by active interference and interfering information effects - Kantsedal, V.M.; Mogyla, А.A. (Radiotekhnika, 2021)
The features of goal-setting control while ensuring the information stability of the sounding modes of a surveillance radar when it is suppressed by active interference and interfering information influences are considered. Overcoming the complexity of goal-setting processes, the validity and efficiency of decision-making with a shortage of time for its adoption is associated with insuring the consistency of goal-setting processes, increasing the levels of their intellectualization and formalization. This will contribute to imparting the desired properties, synthesized during the conflict, to the multipurpose strategies and the situational law of the control of the REP processes and the coordination of actions. An increase in the level of intellectualization of goal-setting processes is ensured by: - decomposition of the general goal-setting problem into separate, simpler subtasks with effective solutions, implemented in the corresponding subsystems of the ACSstab (or basic associations of its functional elements) at stages of information support, preparation, adoption and implementation of the decision at the stages of hierarchical levels of management; - cognitive analysis of goals and reflexive synthesis of goal-setting processes using the capabilities of a specialized intelligent decision support system to enhance the creative-reflexive abilities of the subject of management and increase the level of his professional competencies; - combining the universality of the stages of rational management of the synthesis of the strategy for managing the REP processes with the specifics of conflict situations, subjectivity, cognition and reflexivity nature of intellectual control. Methods and means for partial formalization of goal-setting processes are presented, when the structuring of the main goal is carried out taking into account belonging to the strategies of internal and external control of the REP, the decomposition of the two-sided dynamic model of the conflict between the systems of the RES complex and the radar, the hierarchy of management levels, various approaches applied to goal-setting in a crisis management, as well as methods of justifying goals, resource costs and control of achieving the goals. These features can significantly reduce the degree of subjectivity of management for goal-setting and achieve their validity, completeness, consistency.